Concurrent Neonatal Proteus mirabilis Infection in Dizygotic Twins - Lillian Sung; Noni E MacDonald; James S Hutchison (Canadian Journal of Infectious Diseases)
A case of concomitant infection with Proteus mirabilis in dizygotic twin neonates is presented. The first twin presented with meningitis and septic shock at eight days of age and subsequently died. An investigation of the asymptomatic second twin revealed a urinary tract infection that resolved with antimicrobial therapy. It is recommend that when infection with this virulent organism is diagnosed in one twin, the second twin should be fully evaluated for sepsis and empirical antimicrobial therapy should be considered.